2022
DOI: 10.1038/s41598-022-06320-6
|View full text |Cite
|
Sign up to set email alerts
|

Compound changes in temperature and snow depth lead to asymmetric and nonlinear responses in landscape freeze–thaw

Abstract: Cycles of freeze–thaw (FT) are among the key landscape processes in cold regions. Under current global warming, understanding the alterations in FT characteristics is of a great importance for advising land management strategies in northern latitudes. Using a generic statistical approach, we address the impacts of compound changes in air temperature and snow depth on FT responses across Québec, a Canadian province ~ 2.5 times larger than France. Our findings show significant and complex responses of landscape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…ERA-Interim [7] ), and/or other data variables (e.g. snow water equivalent) could have been included in the portal, the backbone data of CRDAP-QC are limited to the data support used in a number of recent contributions on the FT characteristics in Québec and their variations under changing climate conditions ( [2] , [3] , [4] , [5] ; see the information about the related data article in the specification table above).…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ERA-Interim [7] ), and/or other data variables (e.g. snow water equivalent) could have been included in the portal, the backbone data of CRDAP-QC are limited to the data support used in a number of recent contributions on the FT characteristics in Québec and their variations under changing climate conditions ( [2] , [3] , [4] , [5] ; see the information about the related data article in the specification table above).…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Using the Comparison Tool, the influence of snow depth on FT characteristics can be revealed. Compound impacts on temperature and snow depth in FT characteristics are discussed in details in [5] . By integrating climate, snow and FT data over various spatial scales along with other relevant data such as elevation, as well as location of climate and hydrometric stations, CRDAP-QC can be used for land and water managers in Québec for supporting design, assessment and operational studies.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been hypothesized that the frequency, duration, and intensity of soil freezing in some cold regions might intensify due to lesser snowfall induced by warming winter (Campbell et al, 2010;Groffman et al, 2001;Henry, 2007;Iwata et al, 2010;Kaczmarek et al, 2021;Zhang, 2005). Multiple types of approaches have been carried out on the topic, including modeling studies: Henry (2008), Campbell et al (2010), He et al (2019), Hatami and Nazemi (2022), Zhu et al (2022), andVenalainen et al (2001); observational studies: Qian et al (2011); experimental studies: Iwata et al (2010), Decker et al (2003), Friesen et al (2021), and Hardy et al (2001). Henry (2008) and Campbell et al (2010) reported increasing soil freeze-thaw cycles under future climates with decreasing snow depth (d snow ) through physical and data-driven modeling.…”
mentioning
confidence: 99%
“…• air to soil (Henry, 2008). On the other hand, Hatami and Nazemi (2022) demonstrated that the response of freeze-thaw characteristics combined (of increasing air temperature and decreasing snow depth simultaneously) includes non-linearity. This indicates combined changes in temperature and snow depth to freeze-thaw characteristics could be more intense than only considering the individual change in temperature or snow depth.…”
mentioning
confidence: 99%